Chinese New Year in Siu San Teng Temple, Jambi - Muhamad Safari; C. Dewi Hartati (Fakultas Sastra Universitas Darma Persada, 2019)
Abstract. The existence of Jambi Chinese cannot be separated from the Siu San Teng temple. Siu San Teng Temple is the oldest temple in Jambi which was built in 1805 under the name Hok Tek temple with the main god Hok Tek Tjeng Sin. Siu San Teng Temple as a place of Tridharma worship. As a place of worship for Tridharma, this temple becomes a place of worship during ce it cap go, namely prayers every 1st and 15th of the Chinese calendar. The Chinese New Year celebration at Siu San Teng temple is marked by the Chinese New Year ceremony itself, namely the installation of Chinese New Year candles, prayers to Tian, ​​the main god Hok Tek Tjengsin, the goddess Kwanyim, and the goddess Zhu Sheng Niang Niang. Apart from praying to these gods, the fangsheng tradition is also carried out as a form of getting rid of bad luck and welcoming the arrival of a better new year. The animal released in this tradition is the sparrow. The Chinese New Year at Siu San Teng Temple is also enlivened by liong and lion dance performances.